Excited-state and charge-carrier dynamics in binary conjugated polymer dots towards efficient photocatalytic hydrogen evolution. Issue 4 (6th January 2023) - Liu, Aijie; Wang, Sicong; Song, Hongwei; Liu, Yawen; Gedda, Lars; Edwards, Katarina; Hammarström, Leif; Tian, Haining
Abstract : Tuning the ratio of the donor and acceptor in heterojunction Pdots can greatly influence the charge and energy transfer pathways and dynamics, therefore exhibiting a significant impact on photocatalytic hydrogen production. Abstract : Aqueous dispersed conjugated polymer dots (Pdots) have shown promising application in photocatalytic hydrogen evolution. To efficiently extract photogenerated charges from type-II heterojunction Pdots for hydrogen evolution, the mechanistic study of photophysical processes is essential for Pdot optimization. Within this work, we use a PFODTBT donor (D) polymer and an ITIC small molecule acceptor (A) as a donor/acceptor (D/A) model system to study their excited states and charge/energy transfer dynamics via steady-state and time-resolved photoluminescence spectroscopy, respectively. Charge-carrier generation and the recombination dynamics of binary Pdots with different D/A ratios were followed using femtosecond transient absorption spectroscopy. A significant spectral relaxation of photoluminescence was observed for individual D Pdots, implying an energetic disorder by nature. However, this was not seen for charge carriers in binary Pdots, probably due to the ultrafast charge generation process at an early time (<200 fs). The results showed slower charge recombination upon increasing the ratio of ITIC in binary Pdots, which further resulted in an enhanced photocatalytic hydrogen evolution, twice that as compared to individual D Pdots. Although binary Pdots prepared via the nanoprecipitation method exhibit a large interfacial area that allows high charge generation efficiencies, it also provides a high possibility for charge recombination and limits the further utilization of free charges. Therefore, for the future design of type-II heterojunction Pdots, suppressing the charge carrier recombination via increasing the crystallinity and proper phase segregation is necessary for enhanced photocatalytic hydrogen evolution.